2011
DOI: 10.3758/s13421-011-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and interference in the think/no-think task

Abstract: Five experiments using the think/no-think (TNT) procedure investigated the effect of the no-think and substitute instructions on cued recall. In Experiment 1, when unrelated A-B paired associates were studied and cued for recall with A items, recall rates were reliably enhanced in the think condition and reliably impaired below baseline in the no-think condition. In Experiments 2 and 5, final recall was cued with B items, leading to reliably higher recall rates, as compared with baseline, in both the think and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Finally, memory for all of the target words is tested (e.g., ordeal-r__). Results have shown that recall for the suppressed targets is worse than recall for the baseline targets (on which neither Think nor No-think training has been given), providing the first evidence that intentional suppression is able to cause memory impairment (e.g., Benoit & Anderson, 2012;Bergstrom, de Fockert, & Richardson-Klavehn, 2009;Depue, Curran, & Banich, 2007;Joormann, Hertel, LeMoult, & Gotlib, 2009;Kim & Yi, 2013;Lambert, Good, & Kirk, 2010;Levy & Anderson, 2008;Racsmany, Conway, Keresztes, & Krajcsi, 2012; van Schie, Geraerts, & Anderson, 2013;Waldhauser, Lindgren, & Johansson, 2012). Anderson and Green (2001) suggested that the underlying mechanism of voluntary suppression was different from that of the traditional interference approach.…”
Section: Introductionmentioning
confidence: 96%
“…Finally, memory for all of the target words is tested (e.g., ordeal-r__). Results have shown that recall for the suppressed targets is worse than recall for the baseline targets (on which neither Think nor No-think training has been given), providing the first evidence that intentional suppression is able to cause memory impairment (e.g., Benoit & Anderson, 2012;Bergstrom, de Fockert, & Richardson-Klavehn, 2009;Depue, Curran, & Banich, 2007;Joormann, Hertel, LeMoult, & Gotlib, 2009;Kim & Yi, 2013;Lambert, Good, & Kirk, 2010;Levy & Anderson, 2008;Racsmany, Conway, Keresztes, & Krajcsi, 2012; van Schie, Geraerts, & Anderson, 2013;Waldhauser, Lindgren, & Johansson, 2012). Anderson and Green (2001) suggested that the underlying mechanism of voluntary suppression was different from that of the traditional interference approach.…”
Section: Introductionmentioning
confidence: 96%
“…While the vast majority of the TNT literature supports the notion that intentional cognitive control improves inhibition of retrieval, it has to be stated that some studies did not replicate these results ( Mecklinger et al, 2009 ; Dieler et al, 2010 ). However, participant instructions ( Racsmány et al, 2012 ), demand on cognitive processes and especially working memory as well as strategy might significantly influence behavioral results on the TNT task, which need further exploration ( Raaijmakers and Jakab, 2012 ; Festini and Reuter-Lorenz, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern may tie in with their general cognitive control deficits, given that direct retrieval suppression is presumably cognitively more 745 demanding than thought substitution. Indeed, only the former mechanism is thought to be associated with top-down inhibitory control processes (e.g., Racsmány et al, 2012;Bergström et al, 2009). Therefore, while it is generally fruitful to aid suppression by prescribing a specific mechanism through precise instructions, it is also important to choose a mechanism suitable to the targeted population.…”
Section: Associated With Intrusive Thoughtsmentioning
confidence: 99%
“…However, in many situations, preventing retrieval may also hinder subsequent recall of the unwanted memory by non-inhibitory processes such as associative interference (Verde, 2013;Racsmány, Conway, Keresztes, & Krajcsi, A., 2012;Tomlinson, Huber, Rieth, & Davelaar, 2009;Hertel & Calcaterra, 2005). Interference may particularly 695 contribute to forgetting following thought substitution, which likely strengthens the association between the cue (e.g., TOMATO) and the alternate thought or memory that participants had retrieved (e.g., CLOWN) to prevent the unwanted target memory from coming to mind (e.g.…”
mentioning
confidence: 99%